The Effects of 5-Aza-2`-Deoxycytidine on DLC-1 Gene Expression, Methylation Level and Expression of Downstream Signaling Molecules Cdc42 in Multiple Myeloma - Feng, Xianqi; Zhang, Ling; Nie, Shumin; Su, Zhan; Shi, Xue; Gao, Yan; Chen, Xiangyun; Niu, Wenyuan; Cui, Zhongguang; Zhao, Hongguo; Meng, Fanjun; Zhao, Chunting (Current Signal Transduction Therapy, 2015)
Objective: To investigate the effects of the DNA methyltransferase inhibitor 5-Aza-2'- Deoxycytidine (5-Aza-Dc) on DLC-1 gene expression, methylation level, and the expression of downstream signaling molecules Cdc42 in the human multiple myeloma cell line RPMI8226 cells. Methods: The RPMI8226 cells were treated with 5-Aza-Dc, the methylation status of CpG island of DLC-1 gene was detected by bisulfate sequencing PCR(BSP) in RPMI8226 cells. The expression of DLC-1 and Cdc42 mRNA was determined by reverse transcriptase polymerase chain reaction (RT-PCR). Enzyme-linked immunoabsorbent assay (ELISA) was used to detect the expression of Cdc42 protein. Results: The methylation of DLC-1 gene was detected in the RPMI8226 cells without 5-Aza-Dc pretreament. DLC-1 gene methylation status was decreased after the 5-Aza-Dc treatment for 72h, and DLC-1 gene didn't display DNA methylation on the highest concentration of 5-Aza-Dc. DLC-1 mRNA was weakly expressed in the control group, and the expression was gradually increased in 5-Aza-Dc treatment group. The Cdc42 mRNA and protein expression of experimental group were significantly decreased and were dose-dependent compared with the control group (P <0.05). Conclusion: The results of this research indicated that 5-Aza-Dc can effectively inhibit the methylation status of DLC-1 gene, reversal DLC-1 gene expression, and significantly decrease the expression of downstream signaling molecules Cdc42 mRNA and protein in RPMI-8226 cell.
Keywords: multiple myeloma